2015
DOI: 10.1038/icb.2015.1
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygosity for the common perforin mutation, p.A91V, impairs the cytotoxicity of primary natural killer cells from healthy individuals

Abstract: The production and delivery of functional perforin (PRF; PRF1 gene) by cytotoxic lymphocytes maintains immune homeostasis and tumour immune surveillance. In humans, inheritance of the common PRF1 polymorphism, p.A91V, (c.272C>T) found in 8-9% of the Caucasian population, with another mutated allele resulting in reduced PRF function or trafficking, has been shown to result in hyperinflammatory diseases and/or haematological cancers. In this study, we sought to investigate the function of p.A91V on a wild-type (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 22 publications
3
40
1
Order By: Relevance
“…16,17 Although misfolded A91V PRF is detectable by standard methodologies in healthy A91V heterozygotes, 17 earlier reports suggested that A91V homozygote patients (or those who co-inherited A91V together with a null mutation) have severely reduced or absent PRF levels. 16,18 In analyzing patient II-3, who had bi-allelic A91V mutations but has remained healthy, we demonstrated, for the first time, that A91V homozygosity is indeed compatible with reduced, but still detectable PRF levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 Although misfolded A91V PRF is detectable by standard methodologies in healthy A91V heterozygotes, 17 earlier reports suggested that A91V homozygote patients (or those who co-inherited A91V together with a null mutation) have severely reduced or absent PRF levels. 16,18 In analyzing patient II-3, who had bi-allelic A91V mutations but has remained healthy, we demonstrated, for the first time, that A91V homozygosity is indeed compatible with reduced, but still detectable PRF levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…23 Although hereditary cancer syndromes are typically autosomal dominant with incomplete penetrance, the pattern of inheritance is less clear in this family, with both mono-allelic and bi-allelic carriers of PRF1 mutations developing disease. One explanation for this variable pattern in inheritance is that PRF mutants such as A91V have been previously shown to exhibit dominant negative activity, 17,24 and thus may cause pathology when only present on one allele. Furthermore, although PRF1 mutations may be acting alone, it is possible that another undetected mutation may be present in this family.…”
Section: Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, perforin deficiency is correlated with the onset of other diseases coined perforinopathies [28–30, 44]. However, there is a subset of individuals that have decreased perforin expression and activity but live otherwise healthy lives [24–26]. This is most likely due to the perforin allele having extensive SNVs [18–24, 27, 45].…”
Section: Discussionmentioning
confidence: 99%
“…The most notable of these SNVs is 272C>T resulting in an alanine to valine mutation in the amino acid at position 91 (A91V). Currently, it is reported that 5–20 % of the Caucasian population has this mutation which results in a 50 % decrease in perforin activity when homozygous [26]. The consequence of humans harboring perforin SNVs, resulting in reduced activity, remains to be defined.…”
Section: Discussionmentioning
confidence: 99%